Fraud Patterns in BPK-RI Findings and Strategies to Minimize Corruption in Southeast Sulawesi Local Governments - Burhanuddin Burhanuddin; Wulandari Pryangan; Nita Hasnita (AIBPM Publisher, 2026)
This study aims to analyze fraud patterns found in audit reports by the Audit Board of the Republic of Indonesia (BPK-RI) as an effort to minimize corruption in local governments in Southeast Sulawesi Province. The methods used are descriptive qualitative and quantitative approaches, employing secondary data from the Audit Reports (LHP) and Regional Audit Summaries (IHPD) of BPK-RI for the 2021–2024 period. The analysis was conducted through content analysis to classify findings into expenditure, revenue, assets, administration, and receivables categories, as well as pattern matching to identify recurring fraud modus operandi. The results indicate that fraud is systemic and most predominantly occurs in the expenditure category (47%), particularly in the form of mark-ups, overpayments, and fictitious projects. Four main patterns were identified, including administrative negligence, procurement mark-ups, asset misappropriation, and regional revenue embezzlement. The implications of the study emphasize the need to strengthen internal control systems, digitalize financial governance through e-procurement and e-payment, and implement regulations and a culture of integrity as preventive strategies to minimize corruption in local governments.